Biofouling controls using air bubbles—a review of various applications - Mohd Danial, Ibrahim; Groffer, Nyelang; Dayang Salyani, Abang Mahmod; Aidil Asli, Alias; Yuta, Sunami (Springer Nature, 2025)
Biofouling poses a significant challenge in aquatic, marine, and maritime settings, leading to increased corrosion rates and functional impairments of structures and equipment. Conventional fouling control methods have limitations, prompting the exploration of unconventional approaches to manage biofouling and enhance corrosion resistance. This paper presents a review of employing air bubbles for fouling control in various applications, with a particular focus on marine industries and ecological considerations. By comparing different fouling control techniques, including the use of air bubbles, the paper offers valuable insights into their effectiveness and applicability. Suggestions for future research to develop more efficient techniques for biofouling control using air bubbles are also discussed. This review aims to contribute to the advancement of fouling control strategies and their impact on biofouling characteristics and mitigation efforts.